Program Inovasi Kelas Ibu Muda (IMUD) di Desa Sudimoroharjo di Wilayah Kerja UPTD Puskesmas Wilangan Kabupaten Nganjuk - Siti Asiyah; Hana Febi (STIKES dan AKZI Karya Husada Kediri, 2022)
Maternal and infant health services tend to improve. This is marked by an increase in public access to maternal and infant health services, however, maternal and infant mortality rates are still high. Therefore, preventive efforts are needed to target pregnant women from the 1st trimester. The activity aims to provide understanding and skills regarding healthy pregnancy care. to pregnant women in the first trimester. The implementation approach includes education and focus group talks to build a class plan for young women that is carried out methodically. The method is a cross-program collaboration with the wilangan health facility in the village of Sudimoroharjo, which is a partner for the professional clinical practice of the STIKES Karya Husada midwife, Kediri. by following health regulations, interact directly or face-to-face with expectant mothers. Following an evaluation of the focus group talks, it was decided upon the activity location, the activity schedule, and the key aspects of the material to be presented. 93% of students who completed knowledge questionnaires following educational activities at the first class meeting understood about pregnancy care. The key partners in this service activity's support of educational institutions and locations, as well as initiatives to encourage pregnant women to participate in this activity, are responsible for its success.